Specific Intent in the Croatia V. Serbia Genocide Case: A Critical Appraisal of the ICJ’s Ruling - Saucier Calderón, Jean-Paul (2016)
After having discussed the case’s historical background and the parties’ arguments with emphasis on genocidal intent, the author offers critical comments on the ICJ’s decision. He calls into question the limitations imposed by the Court’s inferential standard and its interpretation in the Croatia v. Serbia case. Although the existence of a plurality of subjective elements in this case did not necessarily entail that there must have been a finding of genocidalintent, it appears that such a plurality has been addressed in a manner that is inconsistent with the Court’s case law, and involves excluding the possibility that genocidal intent may exist concurrently with other non-genocidal subjective elements. The Court’s position overlooks the distinction between motive and intent that has been discussed on many occasions by international criminal tribunals. That distinction could have offered a valuable framework to understand —at least partially— the interplay between different subjective elements displayed in this case. The Court’s questionable position on genocidal intent is also evidenced by its lack of a clear position on the plural reality of intent that encompasses volitional and knowledge elements. Finally, the author engages a discussion on the possibility that the Court has adopted an abstract perspective while an approach focusing on the perpetration of the alleged genocidal acts could have been more respectful of the Convention’s spirit and letter.